Detection of Resistance Mutations in Chronic Hepatitis B Patients Using Antiviral Drugs in Iraq - Abeer Ali Marhoon (Journal of Global Pharma Technology, 2018)
In this study, it is aimed to determine the mutations responsible for drug resistance in patients with chronic hepatitis B virus (HBV) infection received/receiving antiviral treatment at our hospital and to examine the patients in terms of the treatment applied and their HBV-DNA levels. One hundred and eighty-one samples taken from patients diagnosed with chronic hepatitis B infection and follow them between February 2017 till January 2018 at Hepatology and Gastroenterology Teaching Hospital and Central Public Health Laboratory in Baghdad were studied with reverse hybridization principle-based INNO-LiPA HBV DR v2 method and the results were evaluated retrospectively. Mutation was determined in 80 samples (44.1%). and a decrease in DNA level was observed in 101 patients. In INNO LipA reverse hybridization the rtL80V/I mutation was highly frequency among patients 76/80(95%) and followed by rtS202GCI (75%), rtM204V/I/S (72.5%) and rtM250V/I/L (72.5%), rtA194T (67.5%), rtL180M (63.75%), rtT184SCGA (58.75%), rtT184ILFM (31.25%), rtN236T (25%), rtA181T/V (17.5%) and rtV173L (12.5%). This mutation was point mutations a result occurs substitution one nucleotide to another, causing antiviral drugs resistance. Since a limited number of mutations can be examined via INNO LiPA method, it is concluded that different mutation patterns causing drug resistance cannot be determined and it will be beneficial to use an additional method such as sequencing that enables to determine these genes. Additionally, as a result of treatment failure due to drug resistance, if the treatment will be continued with a novel drug that is not used before, it is considered that the possibility of the presence of mutations causing a resistance against this antiviral should not be neglected.